Fikih Informasi : Muhammadiyah’s Perspective on Guidance in Using Social Media - Niki Alma Febriana Fauzi; Ayub Ayub (Indonesian Journal of Islam and Muslim Societies, 2019)
This paper examines a recent product of Muhammadiyah’s collective ijtihad, namely Fikih Informasi (fiqh of information). Fikih Informasi is one of the outcomes of the 30th National Meeting of Majelis Tarjih dan Tajdid (Muhammadiyah’s Council of Religious Affairs). Fikih Informasi represents Muhammadiyah’s attempt to provide guidance for its members and the Muslim community at large, on a usage of social media whch is based on Islamic teachings. The term fikih is an Indonesian word adapted from Arabic word fiqh and Majelis Tarjih’s understanding of the term does not entirely resemble the classical concept of fiqh as understood by majority of Muslim jurists. For this reason, in the first instance this article will explore Majelis Tarjih’s conception of the word fikih then will proceed to examine its application in the context of social media usage. During this process, the paper will argue that Majelis Tarjih employs the term fikih in its literal and Qur’anic meaning rather than using it in its technical sense. As a result, instead of merely referring fikih as the body of legal provisions which it represents, Majelis Tarjih presents fikih as a comprehensive guidance tool, consisting of three level of hierarchically structured norms. As a consquence, Fikih Informasi is not only contains “dos and donts” but also the philosophical principles and sets of values to which users of social media should adhere. In these contexts, this paper critically discusses the limitations of Fikih Informasi, both in its framework and as well as in its content.. Makalah ini membahas produk ijtihad kolektif Muhammadiyah baru-baru ini, yaitu Fikih Informasi. Fikih Informasi adalah salah satu hasil dari Pertemuan Nasional ke-30 Majelis Tarjih dan Tajdid (Dewan Urusan Agama Muhammadiyah) ke-30. Fikih Informasi mewakili upaya Muhammadiyah untuk memberikan panduan bagi para anggotanya dan komunitas Muslim pada umumnya, tentang penggunaan media sosial yang didasarkan pada ajaran Islam. Istilah fikih adalah kata Indonesia yang diadaptasi dari kata Arab fiqh dan pemahaman Majelis Tarjih tentang istilah itu tidak sepenuhnya menyerupai konsep klasik fiqh sebagaimana dipahami oleh mayoritas ahli hukum Islam. Untuk alasan ini, dalam contoh pertama artikel ini akan mengeksplorasi konsepsi Majelis Tarjih tentang kata fikih kemudian akan melanjutkan untuk memeriksa penerapannya dalam konteks penggunaan media sosial. Selama proses ini, makalah ini akan berpendapat bahwa Majelis Tarjih menggunakan istilah fikih dalam arti literalnya dan al-Qur’an daripada menggunakannya dalam pengertian teknis. Akibatnya, alih-alih hanya menyebut fikih sebagai badan ketentuan hukum yang diwakilinya, Majelis Tarjih menghadirkan fikih sebagai alat panduan yang komprehensif, yang terdiri dari tiga tingkat norma terstruktur secara hierarkis. Sebagai konsekuensinya, Fikih Informasi tidak hanya berisi “dos and don’ts” tetapi juga prinsip-prinsip filosofis dan serangkaian nilai yang harus dipatuhi oleh pengguna media sosial. Dalam konteks ini, makalah ini secara kritis membahas keterbatasan Fikih Informasi, baik dalam kerangka kerjanya maupun dalam kontennya.